Efektivitas Metode Iqra’ dalam Mengatasi Buta Aksara Al-Qur’an pada Siswa Kelas III SD Muhammadiyah 1 - Zamzami Zulfa; Salman; Deprizon (Cakrawala: Journal of Religious Studies and Global Society, 2024)
Based on observations and interviews, researchers at the school stated that there were 27 active students in class III who could read the Koran, 3 students and 24 students who were still in the iqra' learning stage. This research aims to find out the application of the iqra' method in overcoming Al-Quran illiteracy. 'an in class III students at SD Muhammadiyah 1 Pekanbaru, and to find out supporting factors and barriers in implementing the iqra method. To find out the best steps in overcoming illiteracy of the Koran at SD Muhammadiyah 1 Pekanbaru. is qualitative research, which aims to explore field data related to problems that have been formulated, using descriptive analysis methods. This research aims to provide an accurate explanation of the application of the Iqra' method in learning the Al-Qur'an to third grade students at SD Muhammadiyah Pekanbaru. The subjects in this research were third grade students at SD Muhammadiyah Pekanbaru, while the object of the research was the Iqra' method which was used to improve the ability to read the Al-Qur'an in the learning process. It can be concluded that the application of the iqra' method in overcoming illiteracy of the Al-Qur'an in class III students at SD Muhammadiyah 1 Pekanbaru. Al-Qur'an learning planning has been carried out including individual tests, class teachers, facilities and infrastructure. For the implementation of Al-Qur'an learning -Qur'an iqra' method, namely opening, apperception, skills/exercise, evaluation and closing. Supporting factors and barriers in implementing the iqra' method in overcoming illiteracy of the Koran at SD Muhamammdiyah 1 Pekanbaru. In a learning process there are several Factors that influence the achievement of learning objectives are supporting and barrier factors. In terms of supporting factors, there is school support, infrastructure and parental cooperation. Barrier factors include the lack of teachers in teaching, the lack of children's ability to learn, the lack of the role of parents in carrying out activities at home.